2021
DOI: 10.1186/s12917-021-03016-3
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo pharmacokinetic study of metformin microparticles as an oral sustained release formulation in rabbits

Abstract: Background Metformin hydrochloride is a biguanide derivative that has been widely used to treat type 2 diabetes in humans. In veterinary medicine, metformin has shown increasing potential for diabetes treatment in different species, such as equids, dogs, cats and rabbits. It is highly hydrophilic, with incomplete gastrointestinal absorption and very large variability in absolute bioavailability between species, ranging from 4% in equids to 60% in humans. Metformin also shows a short half-life o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…The potential burst effect may also lead to overdose and toxicity of the drug. Bouriche et al [39] showed an unexpected decrease in bioavailability of the drug from the microparticles compared with the oral dosage form of the same drug. Additionally, local anesthetics can not only reduce the pain but may also lead to some side effects, such as nerve injury or local anesthetic systemic toxicity [40].…”
Section: Discussionmentioning
confidence: 99%
“…The potential burst effect may also lead to overdose and toxicity of the drug. Bouriche et al [39] showed an unexpected decrease in bioavailability of the drug from the microparticles compared with the oral dosage form of the same drug. Additionally, local anesthetics can not only reduce the pain but may also lead to some side effects, such as nerve injury or local anesthetic systemic toxicity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin in the optimal metformin-loaded ethosome formula (formula #13) did not show a characteristic peak. These findings highlight that metformin was dissolved within the ethosomes during the formulation process (Figure 6) [27].…”
Section: Thermal Analysis Of Optimal Metformin-loaded Ethosomes Formulamentioning
confidence: 91%
“…The pure metformin curve revealed a sharp endothermic peak at 242 • C, while the optimal metformin-loaded ethosome formula (#13) showed a peak appearing at 135 • C, but the thermogram of the empty formula (excipient) revealed two endothermic peaks at 103 • C and 148 • C. Metformin in the optimal metformin-loaded ethosome formula (formula #13) did not show a characteristic peak. These findings highlight that metformin was dissolved within the ethosomes during the formulation process (Figure 6) [27].…”
Section: Thermal Analysis Of Optimal Metformin-loaded Ethosomes Formulamentioning
confidence: 91%
See 2 more Smart Citations